PENGEMBANGAN DESAIN INTERAKTIF SEBAGAI EDUKASI MITIGASI BENCANA TSUNAMI BERBASIS KEARIFAN LOKAL PADA KELURAHAN BARINGIN - Sumema, Sumema; Rotama, Hendra; Gusman, Taufik; Firosha, Ardian; Nissa, Wirda (Wimba : Jurnal Komunikasi Visual, 2025)
Indonesia is vulnerable to tsunami disasters due to its location on the Ring of Fire. Education on tsunami mitigation is extremely important, especially in high-risk areas like Kelurahan Baringin. Local wisdom can be a valuable source of knowledge for this education. Interactive design can be an effective medium for education. The objective of this research is to develop an interactive design for tsunami mitigation education based on local wisdom in Kelurahan Baringin to increase community knowledge and preparedness. The research method will employ a qualitative approach with a design research method. Data will be collected through observation, interviews, and focus group discussions. The outcome will be an interactive design that integrates local wisdom, providing information on tsunamis, mitigation, and local wisdom. The design will be packaged in an engaging and easy-to-understand animated video.